Effectiveness of PTSD treatments for military service members and veterans - Sochenko, Tetyana; Gabińska, Anna (Psychosomatic Medicine and General Practice, 2017)
The core concept of the current review was a description and a discussion of the current situation of treating PTSD among military service members and veterans.This paper is focused solely on combat-related PTSD. It explores guideline recommended interventions for such PTSD, its implication, and efficacy based on the examination of the variety of researches being done around the world.